IMPROVING BEGINNING READING SKILLS OF FIRST GRADE ELEMENTARY LEARNERS THROUGH WORD PUZZLE MEDIA - Ambarwati Imtiyas; Erna Labudasari; Dianasari (Universitas Majalengka, 2025)
This research is motivated by the low initial reading ability of first-grade learners of SD Negeri 1 Pangkalan, Plered District, Cirebon Regency. The research aims to determine the planning, implementation, and improvement of early reading learning using word puzzle media, specifically focusing on the process of saving words. The subjects of this research were 25 first-grade learners. The method used in this research is classroom action research (CAR) with the Kemmis & McTaggart model. This research was conducted in two cycles, each consisting of one meeting, and was divided into four stages: planning, implementation of actions, observation, and reflection. The results showed that the initial reading ability of learners increased from 68% to 98%. This indicates an increase in the initial reading ability of learners through word puzzle media, such as saving words.